2006
DOI: 10.1002/pola.21556
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of liquid‐crystalline block copolymers with cyanoterphenyl moieties by atom transfer radical polymerization

Abstract: A series of new mesomorphic block copolymers composedofdifferentmacroinitiators, including poly(ethylene oxide), polystyrene, and poly(ethylene oxide)‐b‐polystyrene,and polymethacrylate with a pendent cyanoterphenyl group were synthesized through atom transfer radical polymerization. The number‐average molecular weights of the three diblock copolymers, determined by gel permeation chromatography, were 10,254, 9,772, and 15,632 g mol−1, and their polydispersity indices were 1.17, 1.28, and 1.34. The mesomorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…These experimental results complied with the expectations that the RAFT polymerization may be transferred into the ATRP with CPDN acting as the initiator of ATRP when CEH was added. To further validate the experimental results, the CuBr/PMDETA, a typical ATRP catalyst system1, 3, 56–60 was added to the system of RAFT polymerization instead of CEH. The results of the polymerization are presented in Figures 5 and 6, respectively.…”
Section: Resultssupporting
confidence: 82%
“…These experimental results complied with the expectations that the RAFT polymerization may be transferred into the ATRP with CPDN acting as the initiator of ATRP when CEH was added. To further validate the experimental results, the CuBr/PMDETA, a typical ATRP catalyst system1, 3, 56–60 was added to the system of RAFT polymerization instead of CEH. The results of the polymerization are presented in Figures 5 and 6, respectively.…”
Section: Resultssupporting
confidence: 82%
“…Regarding their mesomorphism, all polymers exhibit the nematic phase with mesophasic ranges wider than 200 °C. In our previous studies,25, 26 block copolymers containing conjugated main‐chain fluorene, thiophene, and biphenyl blocks as well as block copolymers containing side‐chain biphenyl‐4‐ylthiophene or cyanoterphenyl blocks possess the smectic A and columnar (Col h and Col r ) phases, but block copolymers consisting of side‐chain biphenyl‐4‐ylfluorene blocks possess the nematic phase. Compared with the smectic A phase of the polymers in our previous studies, the side‐chains of the rigid cores in polymers P1–P4 composed of pendent 4, 4′‐bis(biphenyl)fluorene and biphenyl‐4‐ylfluorene units were separated by the diethyl groups on 9th position of fluorene units which cause the reduction of lateral interaction among rigid rods and thus to favor the nematic phase.…”
Section: Resultsmentioning
confidence: 87%
“…In our previous studies,25, 26 main‐chain block copolymers containing conjugated fluorene, thiophene, and biphenyl backbones as well as side‐chain block copolymers containing biphenyl‐4‐ylthiophene or cyanoterphenyl pendants possess the smectic A and columnar (Col h and Col r ) phases, but side‐chain block copolymers consisting of biphenyl‐4‐ylfluorene pendants possess the nematic phase. Herein, a series of a new mesogenic homopolymer and block copolymer ( P1 and P2 ), which were composed of styrene‐macroinitiators ( SMi ) and methacrylates with pendent 4,4′‐bis(biphenyl)fluorene ( M1 ) groups, were synthesized through ATRP.…”
Section: Introductionmentioning
confidence: 88%
“…Several kinds of rigid cores, including azobenzene [15e17] and biphenyl units [18e23], were applied to mesogenic groups of side-chain LC polymers. In our previous research [24], side-chain LC polymers containing cyanoterphenyl units were also reported to possess mesogenic phases and high stabilities in thermal, chemical, and photochemical properties, but they had poor solubilities. Herein, in order to improve solubility, a series of new mesogenic homopolymers and block copolymers composed of methacrylates containing pendant biphenyl-4-ylthiophene (M1) and biphenyl-4-ylfluorene (M2) groups were synthesized by atom transfer radical polymerization (ATRP), where block copolymers P3 and P4 were produced from styrene macroinitiator (SMi).…”
Section: Introductionmentioning
confidence: 98%
“…H NMR (ppm, CDCl 3 ) d: 0.89 (t, J ¼ 6.9 Hz, 3H), 1.29e1.47 (m, 10H), 1.80 (quintet, J ¼ 6.6 Hz, 2H), 3.98 (t, J ¼ 8.6 Hz, 2H), 6.99 (d, J ¼ 8.8 Hz, 2H), 7.40e7.54 (m, 6H)[24].…”
mentioning
confidence: 98%